Natural language processing and information retrieval principles and applications - Garg, Muskan; Kumar, Sandeep; Khader Jilani Saudagar, Abdul (Computational and intelligent systems series, 2024)
This book presents the basics and recent advancements in natural language processing and information retrieval in a single volume. It will serve as an ideal reference text for graduate students and academic researchers in interdisciplinary areas of electrical engineering